What is Evidence-Based Practice? A Survey of Psychotherapy Service Providers and Leaders in Psychology About Evidence-Based Practice in Psychology - Middleton, Jerry C.; Kalogeropoulos, Christopher; Drapeau, Martin (Canadian Journal of Counselling and Psychotherapy, 2020)
Despite the increased move towards evidence-based practice (EBP), the attitudes towards EBP of psychotherapy providers and of influential leaders in psychology remain underexplored. An online survey was distributed to licensed Canadian psychologists and psychotherapists (n = 684) and leaders (n = 32) in psychology. Leaders were comprised of authors of influential taskforce documents and published reports on EBP in North America, and leaders of psychology regulatory bodies. The survey explored demographics, professional practice characteristics, and attitudes of respondents to questions on psychotherapy practice from the tenets of EBP. Overall, both samples were found attitudinally to be favourably receptive to EBP tenets, although notable differences emerged. Recommendations for continued research into EBP are provided.